TECHNOLOGY TO LENGTHEN OF STORAGE OF CHILI - Jhon David (Agros Journal of Agriculture Science, 2018)
Fresh chili has a very short shelf life, often mechanical and physical damage. Therefore, maximum post harvest handling is needed from harvesting to transportation. If not, it will make the chili soon become damaged, decompose, and experience a higher depreciation rate. The value of damage occurring from the harvesting to the retail level can be around 23 percent. Various technologies have been well designed so that the chili has a longer shelf life. The purpose of this paper is to provide an alternative choice of technology. The method used is the study literature, field survey and secondary data processing from various parties. The study was conducted in 2016. Until now, fresh chilli technology with PP plastic film stored at 10OC with a shelf life of 29 days